A dispersed rutile-TiO2-supported Ni nanoparticle for enhanced gas production from catalytic hydrothermal gasification of glucose. Issue 100 (29th October 2015) - Li, Sha; Zhu, Chao; Guo, Simao; Guo, Liejin
<x xml:space="preserve">Abstract</x> H2 and CH4 production from hydrothermal gasification of glucose was greatly enhanced over a highly dispersed rutile-TiO2-supported Ni nanoparticle.